Co/Fe co-doped porous graphite carbon derived from metal organic framework for microelectrolysis-Fenton catalytic degradation of Rhodamine B. Issue 5 (October 2021) - Liu, Peng; Zhong, Dengjie; Xu, Yunlan; Zhong, Nianbing; He, Guangjun
Abstract: Co/Fe co-doped porous graphite carbon (Co/Fe-PGC) nanocomposites were successfully prepared by one-step pyrolysis with CoFe-MOF, in which the Co/Fe nanoparticles were uniformly coated on porous graphite carbon derived from MOF. It was used to microelectrolysis-Fenton degrade rhodamine B through the main active substance ∙OH. The color and TOC removal rate of 100 mg/L rhodamine B reached 99.41% and 64.6%, respectively, for 30 min. Rhodamine B was degraded into small molecular organic acids, alcohols and lipids by N-demethylation and chromophore cleavage, until it was finally degraded into CO2 and H2 O, and no new colored organics were produced in the degradation process. The degradation process follows the first-order reaction kinetics, and its rate constant is much higher than that of the previous similar studies. The excellent catalytic performance of Co/Fe-PGC catalyst is attributed to the coupling effect of micro-electrolysis and Fenton reaction, and the acceleration of cobalt on electron transport and Fe 2+ reduction. Co 0 /Fe 0 undergoes galvanic corrosion to generate Co 2+ /Fe 2+ and H2 O2, and then these products undergo Fenton reaction to generate Co 3+ /Fe 3+ and ∙OH, thus forming a circulating system of Co 3+ /Fe 3+ and Co 2+ /Fe 2+, enhancing the activation of H2 O2 and ensuring the efficient degradation of RhB. Graphical Abstract: ga1 Highlights: Co/Fe-PGC catalyst was prepared by simple carbonization of MOF precursor. Co/Fe-PGC as IME-Fenton catalyst has high degradation ability for RhB. The addition of Co greatly promoted the activation of H2 O2 . The high activity of the catalyst is attributed to the regeneration of Co 2+ /Fe 2+ . The mechanism of degradation of RhB by Co/Fe-PGC/H2 O2 system was proposed.